Study on Hard and Soft Ticks of Domestic and Wild Animals in Western Iran - Zakkyeh Telmadarraiy; Habibollah Kooshki; Hamideh Edalat; Hassan Vatandoost; Hassan Bakhshi; Faezeh Faghihi; Asadollah Hosseini-Chegeni; Mohammad Ali Oshaghi (Tehran University of Medical Sciences, 2023)
Background: Ticks are blood-sucking ectoparasites of many vertebrates and act as vectors of a wide range of vector-borne diseases. Alongside pathogens transmission, ticks also cause economic losses in animal industry such as production loss, physical damage, anemia, and poisoning. This study aimed to determine the fauna, geographical distribution and seasonal activity of ticks collected from animals in Lorestan Province, west of Iran. Methods: Ticks were collected from domestic animals including cattle, sheep, goats, chickens, turkeys, pigeons, as well as wild animals such as jackals in 2017-2018. Then, they were identified based on morphological characteristics using valid identification keys. Results: Out of a total of 706 ticks, 433 (61.33%), 104 (14.73%), 33 (4.67%) and 136 (19.26%) ticks were collected in spring, summer, autumn and winter, respectively. In terms of hard ticks, 4 genera and 6 species were identified: Hyalomma asiaticum (22.80%), Hyalomma anatolicum (3.68%), Hyalomma marginatum (2.40%), Rhipicephalus sanguineus (0.84%), Dermacentor marginatus (1.13%), and Haemaphysalis sulcata (0.64%). Additionally, two genera and four species fell into soft ticks: Argas persicus (60.48%), Argas reflexus (6.65%), Ornithodoros canstrini (0.70%) and Ornithodoros erraticus (0.42%). There was significant variation in the seasonal activity and abundance of ticks in different seasons but in the tick abundancy among different regions. Conclusions: The present study provides a perspective of the distribution status of ticks in Lorestan Province, their seasonal activity and the likelihood of emergence of related diseases.